"Why do I have to clean teeth regularly?": perceptions and state of oral and dental health in a low-income rural community in Bangladesh - Khan, Antora Mahmud; Ahmed, Syed Masud (BRAC Research and Evaluation Division (RED), 2019)
The general perception that dentistry is expensive keeps many people away from seeking treatment from registered professionals and make them hostage to the services of non-registered lay practitioners. In Bangladesh, no statistics on dental health problems or seeking dental healthcare is available which necessitates study for informed planning of a preventive programme. BRAC Research and Evaluation Division carried out a pilot survey in three unions of Gauripur upazila to document the knowledge and awareness and existing oral hygiene practices among the rural people and also, to explore the care-giving practices of the health care practitioners - both professionals and non-professionals. Both quantitative and qualitative methods were used for data collection. Also clinical examination was done to record their current state of oral cavity. Findings reveal poor oral and dental health condition of the survey population and their lack of knowledge and awareness conducive to good oral and dental health. Findings also reveal their reliance on informal sector providers for treatment of oral and dental health illnesses due to non-availability of qualified professionals. Oral hygiene practice is a neglected chore in the daily routine of the survey population as revealed through real life observation in the study area. The community people hardly used tooth brush and/or tooth paste/powder. Instead, they used various abrasive materials like charcoal powder, branches of trees claimed to have medicinal properties, etc. for cleaning teeth which is damaging, and in turn, cause different oral and dental health problems. The implication of these findings for programme development is discussed.